2004
DOI: 10.1038/sj.eye.6700713
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis and the menstrual cycle

Abstract: Purpose To establish whether there is a variation in the incidence of onset of acute anterior uveitis (AAU) in women during the phases of the menstrual cycle. Methods Prospective open study in women attending the Acute Referral Centre with a first or recurrent attack of AAU. Results There was a significant increase in the incidence of AAU during the late stages of the menstrual cycle. Conclusions The onset of AAU is partially dependent on the levels of either oestrogen or progesterone, or both. The withdrawal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
0
10
0
1
Order By: Relevance
“…We read with interest the article 'Uveitis and the menstrual cycle' by Sanghvi et al 1 In their study, the authors reported the relation between menstrual cycle and patient-reported onset of acute anterior uveitis (AAU), in 76 regularly menstruating women. They concluded that the onset of AAU was partially dependent on the levels of either oestrogen or progesterone, or both.…”
Section: Sir Uveitis and The Menstrual Cyclementioning
confidence: 99%
“…We read with interest the article 'Uveitis and the menstrual cycle' by Sanghvi et al 1 In their study, the authors reported the relation between menstrual cycle and patient-reported onset of acute anterior uveitis (AAU), in 76 regularly menstruating women. They concluded that the onset of AAU was partially dependent on the levels of either oestrogen or progesterone, or both.…”
Section: Sir Uveitis and The Menstrual Cyclementioning
confidence: 99%
“…(Tables 1-2) The difference in uveitis course may relate to the unique sexual hormone milieu of each group. [9] This may correspond to monthly female sex hormone fluctuations during the menstrual cycle in eumenorrheic patients. We also demonstrated an average severity of uveitis flare-up that was more intense in eumenorrheic compared to postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Acharya et al demonstrated that women have been reported to demonstrate more uveitis relapses during the premenstrual and menstrual phases of their cycles. [9] In addition, on our Uveitis Service we have observed that many pregnant women did not relapse during the course of their pregnancy, and instead experienced a severe relapse two to four months after giving Women with idiopathic anterior uveitis do not appear to relapse while pregnant. Relapses are reported more frequently and intensely during premenstrual and menstrual stages.…”
mentioning
confidence: 99%
“…Actualmente se dispone de métodos anticonceptivos hormonales y mecánicos, de administración oral, subcutánea o vaginal (6). Los anticonceptivos que contienen progestina y estrógenos (hormonas presentes en el cuerpo) se encuentran al interior del sistema visual y ocular en el humor acuoso, la glándula lagrimal, las glándulas de Meibomio (GM), el párpado, la conjuntiva bulbar y palpebral, la córnea y la úvea anterior y posterior (7). Existen evidencias que afirman que las glándulas lagrimales y los tejidos superficiales del ojo son sensibles a los cambios en el nivel de estrógenos circulante (8), lo que disminuye el tiempo de rompimiento de la película lagrimal (BUT) y la secreción meibomiana.…”
Section: Introductionunclassified